Tiny thoughts on teamwork - Bezenac, Agnes; Bezenac, Salem (Beirut Dar al Maaref bookshop, 2020)
children discover that doing things together can be a lot more fun. there are also lots of other benefits to doing things as a team!
Education
For children from 3 to 6 years old
1
Keywords: Educational psychology